Sosialisasi Pendampingan Perbaikan Data Stunting Melalui Format Excel - Ashari Taqiudin, Said; Pritamie, Nola; Syahda, Alifia; Akmarti, Salma Rasda; Hamdan, Ahmad (Jurnal Pengabdian Masyarakat Indonesia, 2024)
Stunting is a health issue that is being paid attention to by the world, including Indonesia. Stunting is a chronic nutritional problem that affects the growth and development of children aged 0-59 months and is a global concern. In Indonesia itself, the stunting prevalence rate in Indonesia continues to decline, but has not yet reached the 2024 national target. This community service activity aims to increase the knowledge and understanding of Human Development Cadres (KPM) in reporting stunting data using Microsoft Excel format with the aim of increasing the accuracy and quality of the data. The methods used include lectures, discussions, questions and answers, and assessment of data improvement results by KPM. The results of the activity showed that the socialization was successful in improving the quality and accuracy of stunting data by showing an increase in the percentage of report improvement results, such as in Cimaragas Village from 9.26% to 60% and in Jayaraksa Village from 52.54% to 83%. In conclusion, KPM understands and is able to fill in the data correctly in the format provided